Molecular Analysis of Bacterial Isolates From Necrotic Wheat Leaf Lesions Caused by Xanthomonas translucens, and Description of Three Putative Novel Species, Sphingomonas albertensis sp. nov., Pseudomonas triticumensis sp. nov. and Pseudomonas foliumensis sp. nov. - Tambong, James T.; Xu, Renlin; Gerdis, Suzanne; Daniels, Greg C.; Chabot, Denise; Hubbard, Keith; Harding, Michael W. (Frontiers in Microbiology, 2021)
Xanthomonas translucens is the etiological agent of the wheat bacterial leaf streak (BLS) disease. The isolation of this pathogen is usually based on the Wilbrink’s-boric acid–cephalexin semi-selective medium which eliminates 90% of other bacteria, some of which might be novel species. In our study, a general purpose nutrient agar was used to isolate 49 bacterial strains including X. translucens from necrotic wheat leaf tissues. Maximum likelihood cluster analysis of 16S rRNA sequences grouped the strains into 10 distinct genera. Pseudomonas (32.7%) and Pantoea (28.6%) were the dominant genera while Xanthomonas, Clavibacter and Curtobacterium had 8.2%, each. Erwinia and Sphingomonas had two strains, each. BLAST and phylogenetic analyses of multilocus sequence analysis (MLSA) of specific housekeeping genes taxonomically assigned all the strains to validly described bacterial species, except three strains (10L4B, 12L4D and 32L3A) of Pseudomonas and two (23L3C and 15L3B) of Sphingomonas. Strains 10L4B and12L4D had Pseudomonas caspiana as their closest known type strain while strain 32L3A was closest to Pseudomonas asturiensis. Sphingomonas sp. strains 23L3C and 15L3B were closest to S. faeni based on MLSA analysis. Our data on MLSA, whole genome-based cluster analysis, DNA-DNA hybridization and average nucleotide identity, matrix-assisted laser desorption/ionization-time-of-flight, chemotaxonomy and phenotype affirmed that these 5 strains constitute three novel lineages and are taxonomically described in this study. We propose the names, Sphingomonas albertensis sp. nov. (type strain 23L3CT = DOAB 1063T = CECT 30248T = LMG 32139T ), Pseudomonas triticumensis sp. nov. (type strain 32L3AT = DOAB 1067T = CECT 30249T = LMG 32140T) and Pseudomonas foliumensis sp. nov. (type strain 10L4BT = DOAB 1069T = CECT 30250T = LMG 32142T ). Comparative genomics of these novel species, relative to their closest type strains, revealed unique repertoires of core secretion systems and secondary metabolites/antibiotics. Also, the detection of CRISPR-Cas systems in the genomes of these novel species suggests an acquired mechanism for resistance against foreign mobile genetic elements. The results presented here revealed a cohabitation, within the BLS lesions, of diverse bacterial species, including novel lineages.